The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1007/s00228-011-1092-6
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of asthma medication use among children from a large urban center in Brazil

Abstract: PurposeDespite the advances in asthma therapeutics, there are few data on the use and determinants of anti-asthmatic drugs in the general population of children. This study describes the use of asthma medications among children in the general population and in children with current asthma, living in a large urban center in Brazil.MethodsA population-based cross-sectional survey, aimed at analyzing asthma determinants, was conducted with 1,382 children aged 4–11 years, between February and May 2006, in Salvador… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
2

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 38 publications
0
4
0
2
Order By: Relevance
“…Another potential limitation is the absence of information regarding the effect of treatment on the remission of asthma symptoms. However, in this population, medication for asthma is reported to be highly underused and only one child reported the use of inhaled corticosteroids. Therefore, it was not possible to analyze the data regarding medication.…”
Section: Discussionmentioning
confidence: 83%
“…Another potential limitation is the absence of information regarding the effect of treatment on the remission of asthma symptoms. However, in this population, medication for asthma is reported to be highly underused and only one child reported the use of inhaled corticosteroids. Therefore, it was not possible to analyze the data regarding medication.…”
Section: Discussionmentioning
confidence: 83%
“…Em trabalho com antitérmicos no setor de pediatria do Hospital Santo Antônio de Porto Alegre -RS verificou-se que gotejadores de diversas apresentações disponibilizam volumes/quantidades diversos o que ocasionam erros nas medicações pediátricas disponibilizadas em conta-gotas (SUKIENNIK et al, 2006). Alta variabilidade nas dosagens de medicamentos de uso pediátrico pode implicar em aparecimento de reações adversas, levando a quadros de hospitalizações (SANTOS et al;2012). De acordo com ANVISA e INMETRO, não existem normas técnicas ou regulamentação sobre a utilização de conta-gotas.…”
Section: Resultsunclassified
“…No entanto, sua comercialização está proibida nos Estados Unidos e há relatos de casos de mortes devido ao seu uso na Nova Zelândia (HOFFMAN, 2003). No Brasil, 22% das crianças com quadro asmático são tratadas com fenoterol e a utilização é crescente nessa faixa etária (SANTOS et al, 2012).…”
Section: Introductionunclassified
“…None of wheezing children was receiving controller medications, most had rescue oral bronchodilators for use during exacerbations as their only treatment [25]. Regarding the socioeconomic status, 43.4% of mothers had not completed high school (160/369), the predominant type of constructions was brick houses (354/370, 95.7%) with piped water and sewage system present in 82.7% and 83.6% of them, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…From the survey of 1445 children, the guardians of 417 (28.9%) reported that the children had wheezing in the last 12 months; of these, 374 (89.7% of 417) had complete data set and were included in the present analysis. None of wheezing children was receiving controller medications, most had rescue oral bronchodilators for use during exacerbations as their only treatment [25] . Regarding the socioeconomic status, 43.4% of mothers had not completed high school (160/369), the predominant type of constructions was brick houses (354/370, 95.7%) with piped water and sewage system present in 82.7% and 83.6% of them, respectively.…”
Section: Resultsmentioning
confidence: 99%